2009
DOI: 10.1073/pnas.0809504106
|View full text |Cite
|
Sign up to set email alerts
|

Broad spectrum O-linked protein glycosylation in the human pathogen Neisseria gonorrhoeae

Abstract: Protein glycosylation is an important element of biologic systems because of its significant effects on protein properties and functions. Although prominent within all domains of life, O-linked glycosylation systems modifying serine and threonine residues within bacteria and eukaryotes differ substantially in target protein selectivity. In particular, well-characterized bacterial systems have been invariably dedicated to modification of individual proteins or related subsets thereof. Here we characterize a gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
226
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(240 citation statements)
references
References 33 publications
(36 reference statements)
11
226
1
2
Order By: Relevance
“…Based on mass spectrometric and wet chemical analyses, however, COSY and TOCSY spectra enabled the identification of the monosaccharide units. 1 H chemical shifts and coupling constants allowed the analysis of anomeric configurations. ROESY spectra provided further information about spatial closeness of anomeric protons, which enabled the determination of the interglycosidic linkages.…”
Section: General Description Of the S-layer Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on mass spectrometric and wet chemical analyses, however, COSY and TOCSY spectra enabled the identification of the monosaccharide units. 1 H chemical shifts and coupling constants allowed the analysis of anomeric configurations. ROESY spectra provided further information about spatial closeness of anomeric protons, which enabled the determination of the interglycosidic linkages.…”
Section: General Description Of the S-layer Proteinsmentioning
confidence: 99%
“…In recent years, bacterial glycosylation systems have come under enhanced scrutiny because of the increasing frequencies with which they are seen in pathogenic and symbiont bacteria as well as their potential for exploitation in recombinant glycosylation engineering (1). Interestingly, in several of the investigated bacteria, a scenario of general glycosylation systems and of overlapping roles for distinct carbohydrate-active enzymes is evolving.…”
mentioning
confidence: 99%
“…gonorrheae (11). The second well-characterized type of transfer is sequential and arises in the cytoplasm: glycosyltransferases (GTs) 1 catalyze the transfer of monosaccharide residues, under a nucleotide-diphosphate activated form, in a stepwise manner to the protein.…”
mentioning
confidence: 99%
“…However, both reports used N. meningitidis pilin as the acceptor protein and no information was provided on the ability of PglL to glycosylate other proteins in E. coli or on the presence of an acceptor sequon that is analogous to the one found for N-linked glycosylation. A report by Vik et al (2009) identified 11 O-linked glycoproteins in N. gonorrhoeae but did not find any consensus sequence surrounding the glycosylated amino acids. Instead, they identified the presence of domains of low complexity surrounding the glycosylated amino acids.…”
Section: Alternative Bacterial Glycosylation Systems For Use In Pgctmentioning
confidence: 99%